2005
DOI: 10.1111/j.1365-2125.2005.02550.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical trial comparing an acid‐buffering formulation (ACIDFORM gel) with metronidazole gel for the treatment of symptomatic bacterial vaginosis

Abstract: AimTo compare the effectiveness of an acid-buffering formulation gel (ACIDFORM) with metronidazole gel in the treatment of symptomatic bacterial vag inosis (BV). MethodsAfter a confirmed diagnosis of BV according to the criteria established by Nugent and Amsel, 30 nonpregnant women were enrolled in a randomized, double-blind clinical study. The women were randomly assigned to receive either 5 g ACIDFORM gel ( n = 13) or 10% metronidazole gel ( n = 17) intravaginally once daily for five consecutive days. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…However, it is well known that only a very small percentage of women are able to precisely identify the symptoms of bacterial vaginosis (25). The same is true regarding low rates of persistence of the main symptoms of bacterial vaginosis (14,25).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, it is well known that only a very small percentage of women are able to precisely identify the symptoms of bacterial vaginosis (25). The same is true regarding low rates of persistence of the main symptoms of bacterial vaginosis (14,25).…”
Section: Discussionmentioning
confidence: 79%
“…The length of follow-up is probably the most important variable in evaluating the effectiveness of any treatment for bacterial vaginosis (14). Cure measurements made just after concluding the treatment show higher cure rates (80-90%) than those made 1 month or more after treatment (60-70%) (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycarbophil, in particular, has been widely used for its bioadhesive properties especially after have an interesting buffer role for vaginal pH, this latter product failed to achieve an effectiveness rate similar to that of metronidazole when tested for the treatment of symptomatic VB [59].…”
Section: -Bioadhesive Delivery Systems: Gels Tablets and Filmsmentioning
confidence: 96%
“…Therefore, alternative options for the prophylaxis and treatment of BV, such as oral/vaginal administration of probiotics and vaginal acidification, are being explored (23)(24)(25)(26)(27). In addition, vaginal microbicide formulations designed for the prevention of HIV are currently being examined for their inhibitory effect on BVassociated pathogens given the significant correlation between BV and HIV incidence (28)(29)(30). The phase I safety trial of a microbicide candidate, BufferGel, showed a reduction in the incidence of BV from 30% at enrollment to 6% after 1 week (28).…”
mentioning
confidence: 99%